La valorisation du patrimoine architectural du xxe siècle en Espagne : enjeux et perspectives - Clara Mosquera-Pérez (In Situ)
Contemporary heritage in Spain has coexisted between experiences of preservation and episodes of abandonment and destruction. The architectural production of the 20th century is today the object of a gradual heritage recognition, which undoubtedly benefited from the efforts of international organizations and their promotion campaign. The Spanish Historical Heritage Law of 1985 eliminated the requirement for architectural creations to date to at least a century. However, there is not a particular distinction for this new category of heritage. Its heritage characterisation must be considered, to define the scope of this architectural panorama (modern, regionalist, eclectic achievements, etc.) which represent the creative effervescence of the past century.The starting point was the identification of the heritage values specific to architecture and town planning, already initiated by various authors in the 1980s and 1990s. In addition to the heritage values of authorship and authenticity, others more innovative were added, such as its social dimension, the testimony of an era and the introduction of uses. This plurality was recently incorporated into the National Plan for the Conservation of Cultural Heritage of the 20th century (2015). The identification of threats, the proposal of dissemination, research and intervention methodologies are proposed, accompanied by a collection of databases throughout Spain. The strong autonomy of the Spanish regions in terms of cultural policies poses a real challenge. This national framework provides a global vision that will make it possible to assess the various practices implemented.